APLICAÇÃO DE VITAMINAS EM MILHO PRIMEIRA SAFRA - POLO, Gabriel Furlan; VENDRUSCOLO, Eduardo Pradi; SILVA FILHO, Marcelo Xavier; PATERLINI, Allan; MACHADO, Alexandre Freitas; ALVES, Vitória Carolina Dantas (ANAIS DO ENIC, 2023)
-